MODES OF PLANETARY-SCALE FE ISOTOPE FRACTIONATION - Schoenberg R.; Blanckenburg F.v. (My University, 2006)
A comprehensive set of high-precision Fe isotope data for the principle meteorite types and silicate reservoirs of the Earth is used to investigate iron isotope fractionation at inter- and intra-planetary scales. 14 chondrite analyses yield a homogeneous Fe isotope composition with an average δ56Fe/54Fe value of - 0.015 ± 0.020‰ (2 SE) relative to the international iron standard IRMM-014. Eight non-cumulate and polymict eucrite meteorites that sample the silicate portion of the HED (howardite-eucrite-diogenite) parent body yield an average δ56Fe/54Fe value of - 0.001 ± 0.017‰, indistinguishable to the chondritic Fe isotope composition. Fe isotope ratios that are indistinguishable to the chondritic value have also been published for SNC meteorites. This inner-solar system homogeneity in Fe isotopes suggests that planetary accretion itself did not significantly fractionate iron. Nine mantle xenoliths yield a 2σ envelope of - 0.13‰ to + 0.09‰ in δ56Fe/54Fe. Using this range as proxy for the bulk silicate Earth in a mass balance model places the Fe isotope composition of the outer liquid core that contains ca. 83% of Earth's total iron to within ± 0.020‰ of the chondritic δ56Fe/54Fe value. These calculations allow to interprete magmatic iron meteorites (δ56Fe/54Fe = + 0.047 ± 0.016‰; N = 8) to be representative for the Earth's inner metallic core. Eight terrestrial basalt samples yield a homogeneous Fe isotope composition with an average δ56Fe/54Fe value of + 0.072 ± 0.016‰. The observation that terrestrial basalts appear to be slightly heavier than mantle xenoliths and that thus partial mantle melting preferentially transfers heavy iron into the melt [S. Weyer, A.D. Anbar, G.P. Brey, C. Munker, K. Mezger and A.B. Woodland, Iron isotope fractionation during planetary differentiation, Earth and Planetary Science Letters 240(2), 251-264, 2005.] is intriguing, but also raises some important questions: first it is questionable whether the Fe isotope composition of lithospheric mantle xenoliths are representative for an undisturbed melt source, and second, HED and SNC meteorites, representing melting products of 4Vesta and Mars silicate mantles would be expected to show a similar fractionation towards heavy isotope compositions. This is not observed. Four international granitoid standards with SiO2 contents between 60 and 70 wt.% yield δ56Fe/54Fe values between 0.118‰ and 0.132‰. An investigation of the alpine Bergell igneous rock suite revealed a positive correlation between Fe isotope compositions and SiO2 contents - from gabbros and tonalites (δ56Fe/54Fe ≈ 0.03 to 0.09‰) to granodiorites and silicic dykes (δ56Fe/54Fe ≈ 0.14 to 0.23‰). Although in this suite δ56Fe/54Fe correlates with δ18O values and radiogenic isotopes, open-system behavior to explain the heavy iron is not undisputed. This is because an obvious assimilant with the required heavy Fe isotope composition has so far not been identified. Alternatively, the relatively heavy granite compositions might be obtained by fractional crystallisation of the melt. Ultimately, further detailed studies on natural rocks and the experimental determination of mineral/melt fractionation factors at magmatic conditions are required to unravel whether or not iron isotope fractionation takes place during partial mantle melting and crystal fractionation. © 2006 Elsevier B.V. All rights reserved.
Keywords: CRYSTAL FRACTIONATION; GRANITE; IRON ISOTOPES; PLANETARY DIFFERENTIATION; SOLAR SYSTEM